PEMANFAATAN PLATFORM DIGITAL SEBAGAI SARANA PEMASARAN BAGI UMKM - Natania, Abigael Tesalonika; Dwijayanti, Renny (Jurnal Pendidikan Tata Niaga (JPTN), 2024)
Advances in technology and information have brought significant changes to aspects of human life, one of which is in the field of marketing. This study aims to find out how to use digital platforms as a marketing tool for MSMEs in Kampung Kue. The type of research used is descriptive qualitative. The results of the study stated that the use of digital platforms as a marketing tool for MSMEs in Kampung Kue was less active.